Scott Pilgrim. Vol. 5, Scott Pilgrim vs. the universe - O'Malley, Bryan Lee (Scott Pilgrim, 2009)
This penultimate outing in the graphic novel series, finds Scott in the thick of a happy relationship with the hard-won Ramona V. Flowers, but troubles arise when past indiscretions come to light, leading to some uncomfortable doubts. At the same time, Scott must face down the latest of Ramona's evil ex-boyfriends, the robot-controlling twins Kyle K. ("handsome jerk") and Ken K. ("perfect asshat").